Edukasi Partisipatif Tentang Hasil Hutan Bukan Kayu Bagi Masyarakat Sebagai Upaya Untuk Melestarikan Hutan Kalimantan - Sisillia, Lolyta; Widiastuti, Tri; Roslinda, Emi; Gultom, Kristina Meirito; Sari, Erma (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase community knowledge around Special Purpose Forest Areas (KHDTK) regarding non-timber forest products (HHBK) and increase community awareness and participation in maintaining and utilizing forest products sustainably. The method of implementing this service used participatory-based education. Evaluation of activities used questionnaire instruments and pretest-posttest analysis. To determine the effectiveness of using the service method, use the normalized gain score and the N-Gain effectiveness interpretation category. The results of this service showed that educational activities about HHBK for the community around the KHDTK area of Tanjungpura University, which were carried out in Simpang Kasturi Village were quite effective. The knowledge of the Simpang Kasturi Village community about HHBK increased by 61.4% after educational activities were carried out. People were increasingly aware of the importance of protecting and preserving forests, especially forest areas in Simpang Kasturi Village.